ER stress promotes mitochondrial DNA mediated type-1 interferon response in beta-cells and interleukin-8 driven neutrophil chemotaxis - Vig, Saurabh; Lambooij, Joost M.; Dekkers, Mette C.; Otto, Frank; Carlotti, Françoise; Guigas, Bruno; Zaldumbide, Arnaud (Frontiers in Endocrinology, 2022)
Beta-cell destruction in type 1 diabetes (T1D) results from the combined effect of inflammation and recurrent autoimmunity. Accumulating evidence suggests the engagement of cellular stress during the initial stage of the disease, preceding destruction and triggering immune cell infiltration. While the role of the endoplasmic reticulum (ER) in this process has been largely described, the participation of the other cellular organelles, particularly the mitochondria which are central mediator for beta-cell survival and function, remains poorly investigated. Here, we have explored the contribution of ER stress, in activating type-I interferon signaling and innate immune cell recruitment. Using human beta-cell line EndoC-βH1 exposed to thapsigargin, we demonstrate that induction of cellular stress correlates with mitochondria dysfunction and a significant accumulation of cytosolic mitochondrial DNA (mtDNA) that triggers neutrophils migration by an IL-8-dependent mechanism. These results provide a novel mechanistic insight on how ER stress can cause insulitis and may ultimately facilitate the identification of potential targets to protect beta-cells against immune infiltration.